Preparation method of high-hardness cross-linked modified hydroxy acrylic resin

By preparing hydroxyaramid fibers containing triazinyl chloride compounds and cross-linking with diisocyanate trimers, the problem of poor compatibility between aramid fibers and hydroxyacrylic resins is solved, and the hardness, wear resistance and Flame retardant performance, suitable for high-performance composite materials.

CN118957992BActive Publication Date: 2024-12-13LAIYANG HONGAN CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411426815.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-13
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The prior art is difficult to improve the affinity and compatibility between aramid fiber and hydroxyacrylic resin, resulting in poor hardness, strength and high temperature resistance of hydroxyacrylic resin, limiting its application in high-performance composite materials.

Method used

By preparing methoxy polyaramide containing triazinyl chloride compound, and hydroxy polyaramide is obtained by demethylation reaction of boron tribromide, electrospinning is performed to obtain hydroxyaramid fibers, combining diisocyanate trimers and hydroxyl groups. The acrylic resin undergoes chemical cross-linking reaction to improve the interface performance and compatibility between aramid fiber and resin.

Benefits of technology

The good dispersion of aramid fiber in acrylic resin is achieved, the hardness, wear resistance and tensile properties of the resin are improved, and its flame retardant properties are enhanced, which is the thermal decomposition temperature and ultimate oxygen index of the paint film are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of acrylic resins, and discloses a preparation method of a high-hardness cross-linked modified hydroxy acrylic resin; comprising 100 parts by weight of hydroxy acrylic resin, 1-10 parts by weight of hydroxy aramid fiber, 0.3-0.6 parts by weight of defoamer, 0.3-0.5 parts of wetting and leveling agent, and 2-8 parts by weight of isocyanate trimer. During the curing process, the diisocyanate trimer cross-linking agent reacts with the hydroxyl group of the aramid fiber and the hydroxyl group of the acrylic resin, so that the aramid fiber and the acrylic resin undergo a chemical cross-linking reaction, the interface performance and compatibility between the aramid fiber and the hydroxy acrylic resin are improved, the wear mass loss of the acrylic resin paint film is reduced, the hardness, tensile properties and limiting oxygen index are improved, and the mechanical properties and flame retardant properties are better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic resins, in particular to a method for preparing a high-hardness cross-linked modified hydroxy acrylic resin. Background Art

[0002] Acrylic resins are widely used in materials such as coatings, inks, and castings. When preparing acrylic resins, adding functional monomers such as hydroxyethyl acrylate can produce resins such as hydroxy acrylates with excellent performance, which have better curing, weather resistance, and aging resistance. Improving the hardness, strength, high temperature resistance, and flame retardancy of hydroxy acrylates can expand the practical application of hydroxy acrylic resins in high-performance composite materials.

[0003] Aramid fiber is a polyaromatic amide type synthetic fiber with high mechanical strength, high modulus, strong high temperature resistance and good flame retardant properties. It is widely used in polymer materials such as epoxy resin and acrylic resin. When preparing polyaromatic amide, adding a functional third monomer can give aramid fiber unique properties. The patent with the authorization announcement number CN118271596B discloses a heterocyclic aramid polymer stock solution, heterocyclic aramid fiber and preparation method. The diamine monomer, the heterocyclic third monomer and terephthaloyl chloride are reacted to obtain a heterocyclic aramid fiber with a better affinity with bisphenol A type epoxy resin, which can improve the interlaminar shear strength of the composite material. However, the patent does not improve the affinity and compatibility between aramid fiber and hydroxy acrylic resin, and it is difficult to improve the mechanical, flame retardant and other properties of hydroxy acrylic resin. Summary of the invention

[0004] The invention solves the problem that the hardness, strength and high temperature resistance of hydroxy acrylic resin are poor.

[0005] The technical solution of the present invention is: a method for preparing a high-hardness cross-linked modified hydroxy acrylic resin, comprising the following steps:

[0006] Step (1), adding lithium chloride, a phenylenediamine compound, a phthaloyl chloride compound, and a triazine acyl chloride compound to N,N-dimethylacetamide at 0-5°C, and then reacting at 20-30°C for 4-6 hours, pouring the solution into water, filtering, washing with water and ethanol in turn, and drying to obtain methoxy polyaromatic amide;

[0007] The chemical structural formula of the triazine acyl chloride compound is as follows: ;

[0008] Step (2), add methoxy polyaromatic amide to dichloromethane, introduce nitrogen, dropwise add dichloromethane solution of boron tribromide at 0-5°C, then react at 20-30°C for 12-24h, pour the solution into ice water, filter, wash with water, ethanol, and dry to obtain hydroxy polyaromatic amide. The preparation reaction route is as follows:

[0009] ;

[0010] Step (3), adding hydroxyl polyaramid to N,N-dimethylacetamide, stirring and then standing to degas to prepare a spinning solution with a mass fraction of 12-15%, and then electrospinning at a spinning rate of 0.2-0.6 mL / h, a voltage of 20-25 kV, a receiving distance of 15-20 cm, collecting, and winding to obtain hydroxyl aramid fiber;

[0011] Step (4), adding 1-10 parts by weight of hydroxyaramid fiber to toluene and butyl acetate solvent, ultrasonically dispersing, then adding 100 parts by weight of hydroxy acrylic resin, 0.3-0.6 parts by weight of defoaming agent, 0.3-0.5 parts of wetting and leveling agent, shearing dispersion, and finally adding 2-8 parts by weight of isocyanate trimer to obtain a high hardness cross-linked modified hydroxy acrylic resin.

[0012] Furthermore, in the step (1), the molar ratio of lithium chloride, phenylenediamine compound, phthaloyl chloride compound and triazine acyl chloride compound is (110-120):100:(60-90):(10-40).

[0013] Furthermore, the phenylenediamine compound is p-phenylenediamine or m-phenylenediamine; and the phthaloyl chloride compound is terephthaloyl chloride or isophthaloyl chloride.

[0014] Furthermore, in the step (2), the mass ratio of methoxy polyaromatic amide to boron tribromide is 100:(25-110).

[0015] Furthermore, the isocyanate trimer is hexamethylene diisocyanate trimer, toluene diisocyanate trimer or isophorone diisocyanate trimer.

[0016] Furthermore, the preparation method of the triazine acid chloride compound is:

[0017] S1. Add cyanuric chloride (CAS: 108-77-0), 3-methoxy-4-carboxyphenylboronic acid (CAS: 851335-12-1), tetrakis(triphenylphosphine)palladium, and sodium carbonate in a molar ratio of 1: (3-3.3): (0.07-0.09): (6-7.2) to toluene, add 50-80% water by volume of toluene, heat to 80-100° C. in a nitrogen atmosphere, react for 36-48 hours, distill under reduced pressure to precipitate the precipitate, filter the product, separate it by column chromatography, and use ethyl acetate and petroleum ether solution as eluent to obtain a triazinecarboxylic acid intermediate;

[0018] S2. Add triazine carboxylic acid intermediate to thionyl chloride in a molar ratio of (18-24):1, heat to 65-70°C, react for 6-8h, distill under reduced pressure, and dry to obtain triazine acid chloride compound. The preparation reaction route is as follows:

[0019] .

[0020] Reaction mechanism: The present invention uses cyanuric chloride, 3-methoxy-4-carboxyphenylboronic acid, thionyl chloride and the like as raw materials to prepare a triazine-based acid chloride compound, which is then polymerized with a phenylenediamine compound and a phthaloyl chloride compound to obtain methoxy polyaromatic amide, which is then subjected to a boron tribromide demethylation reaction to obtain hydroxy polyaromatic amide, and finally electrospun to obtain an aramid fiber containing a hydroxyl group and a triphenyl triazine structure.

[0021] Beneficial effects: The present invention adds hydroxyl aramid fiber to the hydroxyl acrylic resin. During the curing process, the diisocyanate trimer crosslinking agent reacts with the hydroxyl group of the aramid fiber and the hydroxyl group of the acrylic resin, thereby realizing a chemical crosslinking reaction between the aramid fiber and the acrylic resin. Through chemical bonding, the interface performance and compatibility between the aramid fiber and the hydroxyl acrylic resin are improved, thereby improving the dispersibility of the aramid fiber in the acrylic resin, making the aramid fiber have a better reinforcement effect, reducing the wear mass loss of the acrylic resin paint film, improving the hardness and tensile properties, and having better wear resistance, hardness and mechanical properties.

[0022] After the cross-linking reaction between the hydroxyaramid fiber and the acrylic resin occurs, the movement of the acrylic resin molecular chain is hindered, the thermal decomposition temperature of the paint film can be increased, and the hydroxyaramid fiber contains a large amount of triphenyl triazine structure, which has strong carbonization property during combustion, and the triazine ring is thermally decomposed to produce non-combustible gases such as nitrogen, which can dilute the oxygen concentration and generate heat during combustion, which is beneficial to improve the limiting oxygen index of the acrylic resin and has better flame retardant performance. DETAILED DESCRIPTION

[0023] The technical scheme of the present invention is further described below through specific examples. The following examples are further explanations of the present invention, but do not limit the scope of the present invention.

[0024] Example 1: The preparation method of triazine acyl chloride compound is:

[0025] S1. Add 6 mmol cyanuric chloride, 19.8 mmol 3-methoxy-4-carboxyphenylboronic acid, 0.54 mmol tetrakis(triphenylphosphine)palladium, 36 mmol sodium carbonate to 50 mL toluene, add 25 mL water, heat to 100°C in a nitrogen atmosphere, react for 36 hours, distill under reduced pressure to precipitate the precipitate, filter the product, and separate it by column chromatography. The eluent is ethyl acetate and petroleum ether solution to obtain a triazine carboxylic acid intermediate. Yield 2.27 g, light yellow solid;

[0026] S2. Add 5 mmol of the triazine carboxylic acid intermediate to 90 mmol of thionyl chloride, heat to 70°C, react for 6 hours, distill under reduced pressure, and dry to obtain a triazine acid chloride compound. Yield: 2.31 g, yellow solid.

[0027] Example 2: The preparation method of triazine acyl chloride compound is:

[0028] S1. Add 6 mmol cyanuric chloride, 18 mmol 3-methoxy-4-carboxyphenylboronic acid, 0.42 mmol tetrakis(triphenylphosphine)palladium, 43.2 mmol sodium carbonate to 50 mL toluene, add 40 mL water, heat to 80°C in a nitrogen atmosphere, react for 48 hours, distill under reduced pressure to precipitate the precipitate, filter the product, and separate it by column chromatography. The eluent is ethyl acetate and petroleum ether solution to obtain a triazine carboxylic acid intermediate. Yield 2.15 g, light yellow solid;

[0029] S2. Add 5 mmol of triazine carboxylic acid intermediate to 120 mmol of thionyl chloride, heat to 65°C, react for 8 hours, distill under reduced pressure, and dry to obtain a triazine acid chloride compound. Yield: 2.37 g, yellow solid.

[0030] Example 3: Preparation method of high hardness cross-linked modified hydroxy acrylic resin:

[0031] (1) At 0°C, add 12 mmol lithium chloride, 10 mmol p-phenylenediamine, 7.5 mmol isophthaloyl chloride, and 2.5 mmol triazine acid chloride compound (prepared according to the method of Example 1) to 25 mL N,N-dimethylacetamide, and then react at 30°C for 4 hours. Pour the solution into water, filter, wash with water, ethanol, and dry to obtain methoxy polyaromatic amide.

[0032] (2) Add 20 g of methoxy polyaromatic amide to 600 mL of dichloromethane, introduce nitrogen, add dropwise 200 mL of dichloromethane solution containing 14 g of boron tribromide at 0°C, and then react at 25°C for 24 hours. Pour the solution into ice water, filter, wash with water, ethanol, and dry to obtain hydroxy polyaromatic amide;

[0033] (3) Add hydroxyl polyaramid to N,N-dimethylacetamide, stir and then stand to degas to prepare a spinning solution with a mass fraction of 12%, and then perform electrospinning at a spinning rate of 0.4 mL / h, a voltage of 22 kV, and a receiving distance of 15 cm. Collect and wind to obtain hydroxyl aramid fiber;

[0034] (4) Add 5 g of hydroxyaramid fiber to 300 mL of toluene and 200 mL of butyl acetate solvent, disperse by ultrasonic, then add 500 g of hydroxy acrylic resin Hongan HU8620, 1.5 g of defoamer AFE-1247, and 2 g of wetting and leveling agent Lencolo 3245, disperse by shear, and finally add 10 g of hexamethylene diisocyanate trimer to obtain a high hardness cross-linked modified hydroxy acrylic resin.

[0035] Example 4: Preparation method of high hardness cross-linked modified hydroxy acrylic resin:

[0036] (1) At 5°C, add 12 mmol lithium chloride, 10 mmol m-phenylenediamine, 9 mmol terephthaloyl chloride, and 1 mmol triazine acid chloride compound (prepared according to the method of Example 1) to 25 mL N,N-dimethylacetamide, and then react at 20°C for 6 hours. Pour the solution into water, filter, wash with water and ethanol in turn, and dry to obtain methoxy polyaromatic amide;

[0037] (2) Add 20 g of methoxy polyaromatic amide to 600 mL of dichloromethane, introduce nitrogen, and dropwise add 80 mL of dichloromethane solution containing 5 g of boron tribromide at 5°C, then react at 20°C for 24 h, pour the solution into ice water, filter, wash with water, ethanol, and dry to obtain hydroxy polyaromatic amide;

[0038] (3) Add hydroxyl polyaramid to N,N-dimethylacetamide, stir and then stand to degas to prepare a spinning solution with a mass fraction of 15%, and then perform electrospinning at a spinning rate of 0.6 mL / h, a voltage of 20 kV, and a receiving distance of 15 cm. Collect and wind to obtain hydroxyl aramid fiber;

[0039] (4) Add 30 g of hydroxyaramid fiber to 300 mL of toluene and 200 mL of butyl acetate solvent, disperse by ultrasonic, then add 500 g of hydroxy acrylic resin Hongan HU8620, 3 g of defoamer AFE-1247, 1.5 g of wetting and leveling agent Lencolo3245, disperse by shear, and finally add 22 g of toluene diisocyanate trimer to obtain a high hardness cross-linked modified hydroxy acrylic resin.

[0040] Example 5: Preparation method of high hardness cross-linked modified hydroxy acrylic resin:

[0041] (1) At 0°C, add 11 mmol lithium chloride, 10 mmol p-phenylenediamine, 6 mmol terephthaloyl chloride, and 4 mmol triazine acid chloride compound (prepared according to the method of Example 1) to 25 mL N,N-dimethylacetamide, and then react at 30°C for 5 h. Pour the solution into water, filter, wash with water, ethanol, and dry to obtain methoxy polyaromatic amide.

[0042] (2) Add 20 g of methoxy polyaromatic amide to 700 mL of dichloromethane, introduce nitrogen, add dropwise 300 mL of dichloromethane solution containing 22 g of boron tribromide at 0°C, and then react at 30°C for 12 h. Pour the solution into ice water, filter, wash with water, ethanol, and dry to obtain hydroxy polyaromatic amide.

[0043] (3) Add hydroxyl polyaramid to N,N-dimethylacetamide, stir and then stand to degas to prepare a spinning solution with a mass fraction of 15%, and then perform electrospinning at a spinning rate of 0.2 mL / h, a voltage of 25 kV, and a receiving distance of 20 cm. Collect and wind to obtain hydroxyl aramid fiber;

[0044] (4) Add 50 g of hydroxyaramid fiber to 300 mL of toluene and 200 mL of butyl acetate solvent, disperse by ultrasonic, then add 500 g of hydroxy acrylic resin Hongan HU8620, 3 g of defoamer AFE-1247, 2.5 g of wetting and leveling agent Lencolo3245, disperse by shear, and finally add 40 g of isophorone diisocyanate trimer to obtain a high hardness cross-linked modified hydroxy acrylic resin.

[0045] Comparative Example 1: Preparation method of high hardness cross-linked modified hydroxy acrylic resin:

[0046] (1) Add 500 g of hydroxyl acrylic resin Hongan HU8620, 1.5 g of defoamer AFE-1247, and 2 g of wetting and leveling agent Lencolo 3245 to 300 mL of toluene and 200 mL of butyl acetate solvent, shear and disperse, and finally add 10 g of hexamethylene diisocyanate trimer to obtain a high-hardness cross-linked modified hydroxyl acrylic resin.

[0047] Comparative Example 2: Preparation method of high hardness cross-linked modified hydroxy acrylic resin:

[0048] (1) At 0°C, add 12 mmol lithium chloride, 10 mmol p-phenylenediamine, and 10 mmol isophthaloyl chloride to 25 mL N,N-dimethylacetamide, and then react at 30°C for 4 hours. Pour the solution into water, filter, wash with water, ethanol, and dry to obtain polyaromatic amide.

[0049] (2) Add polyaramid to N,N-dimethylacetamide, stir and then stand to degas to prepare a spinning solution with a mass fraction of 12%, and then perform electrospinning at a spinning rate of 0.4 mL / h, a voltage of 22 kV, and a receiving distance of 15 cm. Collect and wind to obtain aramid fibers;

[0050] (3) Add 5 g of aramid fiber to 300 mL of toluene and 200 mL of butyl acetate solvent, disperse by ultrasonic, then add 500 g of hydroxyl acrylic resin Hongan HU8620, 1.5 g of defoamer AFE-1247, and 2 g of wetting and leveling agent Lencolo 3245, disperse by shear, and finally add 10 g of hexamethylene diisocyanate trimer to obtain a high hardness cross-linked modified hydroxyl acrylic resin.

[0051] Comparative Example 3: Preparation method of high hardness cross-linked modified hydroxy acrylic resin:

[0052] (1) Add methoxy polyaramid (prepared according to the method of Example 3) to N,N-dimethylacetamide, stir and let stand for degassing to prepare a spinning solution with a mass fraction of 12%, and then perform electrospinning at a spinning rate of 0.4 mL / h, a voltage of 22 kV, and a receiving distance of 15 cm. Collect and wind to obtain methoxy aramid fiber.

[0053] (2) Add 5 g of methoxyaramid fiber to 300 mL of toluene and 200 mL of butyl acetate solvent, disperse by ultrasonic, then add 500 g of hydroxyl acrylic resin Hongan HU8620, 1.5 g of defoamer AFE-1247, and 2 g of wetting and leveling agent Lencolo3245, disperse by shear, and finally add 10 g of hexamethylene diisocyanate trimer to obtain a high hardness cross-linked modified hydroxyl acrylic resin.

[0054] The high temperature resistant hydroxyl acrylic resin was cured at 80°C for 5 hours to form a paint film.

[0055] The wear resistance of the paint film was tested in an abrasion tester according to GB / T 1768-2006 standard, with a grinding wheel load of 1000g, a rotation speed of 200r / min, and a revolution of 1000r, and the mass loss before and after wear was measured.

[0056] The hardness of the paint film is measured by the pencil method in accordance with GB / T 6739-2022.

[0057] The tensile properties of the high temperature resistant hydroxyl acrylic resin cured film were tested according to GB / T 1040.1-2018 standard using an electronic tensile testing machine at a tensile rate of 50 mm / min. The test results are shown in Table 1.

[0058] Table 1: Performance test results of Examples 3-5 and various comparative examples

[0059]

[0060] The flame retardant properties of the paint film are tested according to GB / T 2406.1-2008 standard.

[0061] The thermal properties of the film were tested in a thermogravimetric analyzer under a nitrogen atmosphere, with the temperature increased to 800°C at a heating rate of 10°C / min. The test results are shown in Table 2.

[0062] Table 2: Performance test results of Examples 3-5 and various comparative examples

[0063]

[0064] As can be seen from the above table, compared with Comparative Example 1, hydroxyl aramid fiber and diisocyanate trimer are added to the hydroxyl acrylic resin in Examples 3 to 5. During the curing process, the diisocyanate trimer acts as a crosslinking agent to react with the hydroxyl groups of the aramid fiber and the hydroxyl groups of the acrylic resin, thereby achieving a chemical crosslinking reaction between the aramid fiber and the acrylic resin. Through chemical bonding, the interface performance and compatibility between the aramid fiber and the hydroxyl acrylic resin are improved, thereby improving the dispersibility of the aramid fiber in the acrylic resin, making the aramid fiber have a better reinforcement effect, reducing the wear quality loss of the acrylic resin paint film, improving the hardness and tensile properties, and having better wear resistance, hardness and mechanical properties. In addition, after the aramid fiber undergoes a crosslinking reaction with the acrylic resin, the movement of the acrylic resin molecular chain is hindered, which can increase the thermal decomposition temperature of the paint film. At the same time, it contains a large amount of triphenyl triazine structure ( ), the carbon-forming property is very strong when burning, and the pyrolysis of triazine ring produces non-flammable gases such as nitrogen, which can dilute the oxygen concentration and generate heat during combustion, which is beneficial to improve the limiting oxygen index of acrylic resin and have better flame retardant properties.

[0065] In Comparative Example 2, no triazine chloride compound was added during the preparation of polyaramid, and the obtained aramid fiber did not contain hydroxyl groups, and could not undergo a cross-linking reaction with diisocyanate trimer and hydroxy acrylic resin. The compatibility between the aramid fiber and the acrylic resin was very poor, and the reinforcement effect was not good. The wear resistance, hardness and tensile properties of the acrylic resin were not good, and the aramid fiber did not contain a triphenyl triazine structure. The limiting oxygen index of the acrylic resin was low, and the flame retardant properties were not good.

[0066] The methoxy aramid fiber prepared in Comparative Example 3 does not contain hydroxyl groups and cannot undergo cross-linking reaction with diisocyanate trimer and hydroxy acrylic resin. The acrylic resin has poor wear resistance, hardness and tensile properties, and a low thermal decomposition temperature.

[0067] It can be understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing a high-hardness cross-linked modified hydroxy acrylic resin, characterized in that: The following steps are involved: Step (1), adding lithium chloride, a phenylenediamine compound, a phthaloyl chloride compound, and a triazine acyl chloride compound to N,N-dimethylacetamide at 0-5°C, and then reacting at 20-30°C for 4-6 hours, pouring the solution into water, filtering, washing, and drying to obtain methoxy polyaromatic amide; The chemical structural formula of the triazine acyl chloride compound is as follows: ; Step (2), adding methoxy polyaromatic amide to dichloromethane, introducing nitrogen, adding dropwise a dichloromethane solution of boron tribromide at 0-5°C, and then reacting at 20-30°C for 12-24h, pouring the solution into ice water, filtering, washing, and drying to obtain hydroxy polyaromatic amide; Step (3), adding hydroxyl polyaramid to N,N-dimethylacetamide, stirring and then standing to degas to prepare a spinning solution, and then electrospinning, collecting, and winding to obtain hydroxyl aramid fibers; Step (4), adding 1-10 parts by weight of hydroxyaramid fiber to toluene and butyl acetate solvent, ultrasonically dispersing, then adding 100 parts by weight of hydroxy acrylic resin, 0.3-0.6 parts by weight of defoaming agent, 0.3-0.5 parts of wetting and leveling agent, shearing dispersion, and finally adding 2-8 parts by weight of isocyanate trimer to obtain a high hardness cross-linked modified hydroxy acrylic resin.

2. The method for preparing a high-hardness cross-linked modified hydroxy acrylic resin according to claim 1, characterized in that: In the step (1), the molar ratio of lithium chloride, phenylenediamine compound, phthaloyl chloride compound and triazine acyl chloride compound is (110-120):100:(60-90):(10-40).

3. The method for preparing a high-hardness cross-linked modified hydroxy acrylic resin according to claim 2, characterized in that: The phenylenediamine compound is p-phenylenediamine or m-phenylenediamine; the phthaloyl chloride compound is terephthaloyl chloride or isophthaloyl chloride.

4. The method for preparing a high-hardness cross-linked modified hydroxy acrylic resin according to claim 1, characterized in that: In the step (2), the mass ratio of methoxy polyaromatic amide to boron tribromide is 100:(25-110).

5. The method for preparing a high-hardness cross-linked modified hydroxy acrylic resin according to claim 1, characterized in that: In the step (3), the mass fraction of the spinning solution is 12-15%; the spinning rate during electrospinning is 0.2-0.6 mL / h, the voltage is 20-25 kV, and the receiving distance is 15-20 cm.

6. The method for preparing a high-hardness cross-linked modified hydroxy acrylic resin according to claim 1, characterized in that: The isocyanate trimer is hexamethylene diisocyanate trimer, toluene diisocyanate trimer or isophorone diisocyanate trimer.

7. The method for preparing a high-hardness cross-linked modified hydroxy acrylic resin according to claim 2, characterized in that: The preparation method of the triazine acid chloride compound is: S1. Add cyanuric chloride, 3-methoxy-4-carboxyphenylboronic acid, tetrakis(triphenylphosphine)palladium, sodium carbonate and water to toluene, heat to 80-100° C. in a nitrogen atmosphere, react for 36-48 hours, distill under reduced pressure to precipitate the precipitate, filter the product and separate it by column chromatography to obtain a triazine carboxylic acid intermediate; S2. Add triazine carboxylic acid intermediate to thionyl chloride, heat to 65-70° C., react for 6-8 hours, distill under reduced pressure, and dry to obtain a triazine acid chloride compound.

8. The method for preparing a high-hardness cross-linked modified hydroxy acrylic resin according to claim 7, characterized in that: In the S1, the molar ratio of cyanuric chloride, 3-methoxy-4-carboxyphenylboric acid, tetrakis(triphenylphosphine)palladium and sodium carbonate is 1:(3-3.3):(0.07-0.09):(6-7.2).

9. The method for preparing a high-hardness cross-linked modified hydroxy acrylic resin according to claim 7, characterized in that: In the S1, the volume ratio of toluene to water is 1:(0.5-0.8).

10. The method for preparing a high-hardness cross-linked modified hydroxy acrylic resin according to claim 7, characterized in that: In the S2, the molar ratio of thionyl chloride to triazine carboxylic acid intermediate is (18-24):1.